Lydia the reading fairy - Meadows, Daisy (London : Orchard Books, 2016)
Lydia the Reading Fairy's magical badge has been stolen by Jack Frost. Without it, all reading lessons are ruined! Can Rachel and Kirsty help their magical friend make reading fun for everyone again?
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction